Kajian kelayakan kualitas air untuk budidaya ikan sistim kurungan jaring tancap di Kelurahan Urongo - Duyoh, Marini; Pangemanan, Novie P. L.; Kusen, Diane J.; Kalesaran, Ockstan J.; Undap, Suzanne L.; Tumembouw, Sipriana S. (Universitas Sam Ratulangi, 2023)
The fishery sector which has great profit prospects can still be developed by cultivating fish better by paying attention to the condition of the water quality. In fish farming, it is very important to study water quality conditions because water quality parameters are a limiting and life-supporting factor for the types of aquatic biota cultivated in a waters including tilapia (Oreochromis niloticus. This research was conducted to assess water quality, both physical, chemical, and aquatic biology of Lake Tondano to support the feasibility test activities of Lake Tondano waters for Cage Netting Cage cultivation media. The research method used was purposive sampling. Primary data comes from primary data which is the result of measurements of physico-chemical parameters of water quality directly in the field (in situ) and supported by secondary data on several physical and chemical parameters of Lake Tondano waters as well as data on water quality of the cultivation media with the Netting Cage system. The physical and chemical parameters of Lake Tondano waters at the three stations were analyzed using the suitability scoring method for the location of Tondano Lake waters to be used as a maintenance medium fish with a Stuck Net Containment system. The results of the study concluded that the physical and chemical quality of water in Urongo waters was suitable for net cage culture. Keywords: physical-chemical parameters, Lake Tondano, aquaculture, Nile tilapia